2021
DOI: 10.1186/s13099-021-00399-4
|View full text |Cite
|
Sign up to set email alerts
|

The genomic characterisation and comparison of Bacillus cereus strains isolated from indoor air

Abstract: Background Bacillus cereus is ubiquitous in nature, found in environments such as soil, plants, air, and part of the insect and human gut microbiome. The ability to produce endospores and biofilms contribute to their pathogenicity, classified in two types of food poisoning: diarrheal and emetic syndromes. Here we report gap-free, whole-genome sequences of two B. cereus strains isolated from air samples and analyse their emetic and diarrheal potential. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The detection of acquired antimicrobial resistance genes by two different programs in conjunction with two different databases resulted in a different number of detected genes. Premkrishnan et al also identified discrepancies in the number of detected antimicrobial resistance genes when using different methods for the detection of ARGs ( 42 ). This finding shows the importance of using multiple ARG detection tools to improve the detection of antimicrobial resistance genes ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of acquired antimicrobial resistance genes by two different programs in conjunction with two different databases resulted in a different number of detected genes. Premkrishnan et al also identified discrepancies in the number of detected antimicrobial resistance genes when using different methods for the detection of ARGs ( 42 ). This finding shows the importance of using multiple ARG detection tools to improve the detection of antimicrobial resistance genes ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…Premkrishnan et al also identified discrepancies in the number of detected antimicrobial resistance genes when using different methods for the detection of ARGs ( 42 ). This finding shows the importance of using multiple ARG detection tools to improve the detection of antimicrobial resistance genes ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…These data support the hypothesis that E. amstelodami is a rich resource for mining novel SMs. Similarly, Bacillus species are common gram-positive bacterium detected in the air ( Premkrishnan et al, 2021 ), water ( Mothe and Sultanpuram, 2016 ), soil ( Lim et al, 2016 ), and fermented foods ( Wu et al, 2022 ). Various Bacillus members (e.g., Bacillus licheniformis , Bacillus subtilis , and Bacillus amyloliquefaciens ) are extensively used in the production of bioinsecticides and antibiotics due to their ability to synthesize a number of metabolites with biological activity ( Xu et al, 2014 ; Yang et al, 2016 ; Shahzad et al, 2017 ; Mohamad et al, 2018 ), indicating a great potential for SM synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of acquired antimicrobial resistance genes by two different programs in conjunction with two different databases resulted in a different number of detected genes. Premkrishnan et al also identified discrepancies in the number of detected antimicrobial resistance genes when using different methods for the detection of genes (38). This finding shows the importance of using multiple AMR gene detection tools to improve the detection of antimicrobial resistance genes (38).…”
Section: Resultsmentioning
confidence: 98%
“…Premkrishnan et al also identified discrepancies in the number of detected antimicrobial resistance genes when using different methods for the detection of genes (38). This finding shows the importance of using multiple AMR gene detection tools to improve the detection of antimicrobial resistance genes (38).…”
Section: Resultsmentioning
confidence: 98%